Biomass Production of Eucalyptus tereticornis in Different Agroecological Regions of India - Rawat, Vijay; Negi, J. D. S. (Indian Forester, 2004)
Climate inter alia is the strongest ecological factor in determining the primary production. Eucalyptus terelicornis (Mysore Gum) is most widely planted species in India. In the present paper an attempt has been made to assess the primary production of the species in different agroecological regions of India. Depending on length of growing period (LGP) and precipitation, country has been divided into six agroecological zones and available data on biomass production has been stratified into different agroecological zones. In general biomass varied from 11.9 t/ha in three year old plantation to 146 than in 9 year old plantation in moist regions. In dry tropical region it varied from 5.65 t/ha in 5 year plantation to 135.5 t/ha in 9 year old plantation. In dry tropical regions biomass accumulation was more in cooler areas as compared to warmer areas. Where water is not the limiting factor comparatively higher mean annual temperature of around 25Â°C seems to produce higher biomass. A higher share of leaf biomass was observed in dry region. The rootl/shoot ratio was also higher in dry tropical region.